Alphabetic Flash Cards Improve English Alphabet Writing and Spelling Accuracy - Deajeng A'ida Mustafa; Vidya Mandarani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Foundational literacy skills, particularly alphabet writing and spelling, are essential for early English language acquisition and require instructional approaches that address diverse learning styles. Specific Background: Alphabetic flash card media, as a visual and kinesthetic learning tool, facilitates letter recognition, phonemic awareness, and memory retention through interactive engagement. Knowledge Gap: Despite its simplicity and theoretical support from multisensory learning principles, flash card media remains underutilized in formal classrooms dominated by conventional teaching methods. Aims: This study investigates the use of alphabetic flash cards to develop learners’ ability to write and spell English alphabetically. Results: Findings indicate that students taught using flash cards demonstrated higher spelling accuracy and greater writing fluency than those receiving traditional instruction. Novelty: The study highlights the practical value of a low-cost, multisensory instructional medium that simultaneously supports visual, kinesthetic, and cognitive processing in beginner English learners. Implications: Integrating alphabetic flash cards into early literacy instruction can strengthen foundational English skills and increase student participation, suggesting their suitability for beginner EFL contexts and future adaptation into digital learning platforms.Highlights: Learners using card-based activities produced more correct letter sequences than peers in conventional classes. Interactive visual-kinesthetic tasks supported stronger phoneme–grapheme connections during basic literacy practice. Classroom participation increased when multisensory materials replaced lecture-centered instruction. Keywords: Alphabetic Flash Cards; Alphabet Writing; Spelling Accuracy; Early Literacy; English Learning